Penghayatan Umat Paroki St. Antonius Padua Pasuruan atas Makna Paroki menurut KHK 515 - Vinsensius Rixnaldi Masut; Elfridus Cancang (Sekolah Tinggi Teologi Tenggarong, 2021)
The focus of this study is to describe how the parishioners of St. Antony of Padua Parish, Pasuruan, understand the parish as a community of the Christian faithful according to Can. 515. This understanding is inspired by the spirit of Vatican II which views the Church as a community of God's people on pilgrimage in the world. The methodology used in this study is a qualitative and phenomenological research exploring their daily way of life. The author conducted in-depth interviews with the parishioners of St. Antony of Padua, Pasuruan. The interview results were then elaborated on the meaning of a parish according to Can. 515. The findings of this study are: (1) The parish as a community of Christian believers plays an important role in realizing the Church as a communion of God's people. (2) The parishioners awareness is revealed in active participation in church activities and pastoral care.AbstrakFokus studi ini ialah mendeskripsikan penghayatan umat Paroki St. Antonius Padua Pasuruan terhadap pengertian paroki sebagai komunitas kaum beriman Kristiani menurut KHK 515. Pemaknaan ini diinsipirasi oleh semangat Konsili Vatikan II yang merefleksikan Gereja sebagai persekutuan umat Allah yang sedang berziarah di dunia. Paroki sebagai bagian dari Gereja universal mempunyai peranan yang sangat penting dalam menghantar umat untuk mewujudkan persekutuan tersebut. Metodologi yang digunakan dalam studi ini ialah penelitian kualitatif dan fenomenologis yang menggali mental atau aktus kehidupan manusia dalam keseharian hidupnya. Penulis melakukan depth interview (wawancara mendalam) terhadap umat Paroki St. Antonius Padua Pasuruan. Hasil wawancara kemudian dielaborasi dengan pengertian paroki menurut KHK 515. Temuan dari studi ini ialah: (1) Paroki sebagai komunitas kaum beriman Kristiani memainkan peran penting dalam mewujudkan persekutan umat Allah sebagaimana makna Gereja itu sendiri. (2) Kesadaran umat akan makna paroki terungkap dalam partisipasi aktif dalam kegiatan menggereja dan reksa pastoral.